Inclusion of Blend of L-lysine, DL-Methionine and Vitamins D3, E in Diets for Broiler; Effects on Growth Performance, Feed Intake and Conversion and Water Intake. - Rani Abro; Abdul Ghaffar; Shahid Hussain Abro; Hakimzadi Wagan; Ahmed Nawaz Tunio; Jameel Ahmed Gandahi; Pershotum Khatri; Huma Rizwana; Riaz Ahmed Leghari; Bakhtawar Wagan; Mohsan Ullah Goraya (Journal of Basic & Applied Sciences, 2016)
The blend comprising of L-lysine, DL-methionine and vitamins D3, E in diets evaluated for growth performance, water intake, feed consumption and conversion ratio and live body weight in broiler was investigated. The study was performed on 360 day old broiler chickens and divided into four groups i.e. A (control), B,C and D (30 chickens in each group) randomly. The birds were fed blend in the diets; group B (40gm / 50 kg feed), group C (80 gm / 50 kg feed) and group D (120 gm / 50 kg feed). The growth parameters of broilers were significant (P<0.05) high in the diet group D in comparison to C, B and A groups respectively. The broiler in group D consumed more feed (4303.20 g/bird) followed by the broiler in C, B and A groups respectively. The significant difference (P<0.05) was determined in water intake of broilers among the groups. The broiler in group D was gained more live body weight (2301.60 g/bird) followed by the broilers in C (2094.50), B (2009.00) and A (1922.20 g/bird). The broiler in group D resulted superior feed conversion efficiency (1.87); followed by the broilers in group C (1.97). The broiler in groups B and A (control) resulted in lowest feed conversion efficiency (1.99 and 2.00) respectively. Overall, the supplementation of the blend in feed 120gm / 50 kg significantly influence on the feed consumption, water intake, live body weight and growth performance in broiler chickens.